The influence of functional groups on the ethylene polymerization performance of silsesquioxane-supported Phillips-type catalysts. Issue 36 (4th September 2017) - Baba, Ryuki; Thakur, Ashutosh; Chammingkwan, Patchanee; Terano, Minoru; Taniike, Toshiaki
Abstract : A series of silsesquioxane-supported Phillips-type molecular catalysts for ethylene polymerization were synthesized by introducing various functional groups in proximity to monoalkylated Cr(iii ). Abstract : A series of silsesquioxane-supported Phillips-type molecular catalysts for ethylene polymerization were synthesized by introducing various functional groups in proximity to monoalkylated Cr(iii ). They were moderately active in ethylene polymerization, while the performance was sensitive to the type of functional group. In particular, the presence of a lone pair near the active center was found to enhance the activity and expand the molecular weight distribution, which is plausibly due to alkylaluminum temporally captured by the lone pair. A similar result was never obtained by adding free molecules bearing a lone pair, and the fixation of the lone pair near the active site was essential. It was revealed that the design strategy based on the support functionalization can be transferred to SiO2 -supported chromium catalysts.